Students Variables and the Development of Employability Mastery on Undergraduates Business Education Students in Federal Universities in Southern Nigeria - Cletus Akpo Atah; Basil Nwosu; Emanuel Bessong (Richtmann Publishing, 2022)
The study examined Students Variables and the development of employability mastery on undergraduates Business Education Students in Federal Universities in Southern Nigeria. Two research questions and two null hypotheses were developed to direct the investigation in order to fulfil the study's objectives. For the study, a survey research design was used. 440 students in their final year of business study made up the population. Data were gathered using a 20-item survey called the